Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.33899/ijvs.2021.126906.1410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on protoscoleces of Echinococcus granulosus in vitro and in vivo

Abstract: The current study was designed to investigate the effect of ultrasound on the protoscoleces of Echinococcus granulosus by enforcing steady numeral of frequencies during a certain interval (20000 pulse/s) (1.8 w/cm 2 ), using exposure time 30,20,15,12,10 and 5s, individually and respectively. Consequently, six albino mice groups were immunized against cystic echinococcosis, which injected with exposed protoscoleces, to acquire specific cell-mediated immunity, called delayed type-hypersensitivity (DTH) which ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Many techniques were used against infestation with hydatid disease in experiential animals, such as irradiation with laser, direct electrical current, probiotics and ultrasound (31)(32)(33)(34)(35)(36)(37), all techniques revealed considerable influence to the disease. All the techniques exhibited valuable efficiency against protoscoleces in vitro and cystic echinococcosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques were used against infestation with hydatid disease in experiential animals, such as irradiation with laser, direct electrical current, probiotics and ultrasound (31)(32)(33)(34)(35)(36)(37), all techniques revealed considerable influence to the disease. All the techniques exhibited valuable efficiency against protoscoleces in vitro and cystic echinococcosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran abattoirs, Pezeshki reported that; the prevalence of E. granulosus parasite's larva stage or hydatidosis disease which is a remarkable silent zoonotic helminthic malady infection in intermediate hosts warm-blooded vertebrates as cattle and sheep which is 2.25% and 2.48%, respectively and what is worth to mention the definitive host includes carnivores such as the canidae and felidae families such as dogs, foxes and hyenas, according to a survey created for the period 2015 -2018, (12,13) The overall prevalence in Pakistan during the period 2000 -2020 is 18.1%, with the highest infection in sheep 53.5%, followed by goats 44.9%, cows 21.3%, buffaloes 16.8%, and cattle 12.7% (14,15). In slaughtered sheep and goats in Amol abattoir, Mazandaran, northern Iran, the prevalence rate of Fasciola spp was 6.6% (16,17). The infection rates of the Fasciola parasite in sheep in Jeddah, Saudi Arabia, is higher among the imported sheep 1.19% than local slaughtered sheep 0.27% in the period 2019-2020 (18,19).…”
Section: Introductionmentioning
confidence: 99%